2020
DOI: 10.1186/s12875-020-01301-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between patient activation measurement and self-rated health in patients with chronic diseases

Abstract: Background In the aging population, chronic diseases and multimorbidity are common. Therefore, it is important to engage patients in their self-care. The aim of this study was to analyze the relationship between activity in self-care and self-rated health among primary care patients with chronic diseases. Methods The data of the present study were derived from a research project on the Participatory Patient Care Planning in Primary Care (4PHC). A total of 605 patients were recruited in the Siilinjärvi Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
(55 reference statements)
0
13
3
2
Order By: Relevance
“…Additionally, researchers have indicated that high levels of activation in disease management help patients achieve the best possible quality of life and diminish the risk factors of their chronic disease. 5 , 6 …”
Section: The Impact Of Behavioral Interventions On Patient Activation...mentioning
confidence: 99%
“…Additionally, researchers have indicated that high levels of activation in disease management help patients achieve the best possible quality of life and diminish the risk factors of their chronic disease. 5 , 6 …”
Section: The Impact Of Behavioral Interventions On Patient Activation...mentioning
confidence: 99%
“…However, compared with other countries in this survey, Japan had the highest proportion of participants with level 1 PAM (70.45%), implying that participants from Japan were not as engaged in self-management of wet AMD, possibly as a result of cultural differences [ 26 , 36 ]. Self-rated health and PAM have a significant linear relationship, specifically in patients with chronic conditions [ 37 , 38 ]. In addition to tailoring treatment for patients, a higher self-reported PAM score is associated with medication adherence, self-management approach of the patients, and improved QoL [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these diseases, patients could also have other diseases. The baseline results have been presented in more detail in our previous article [ 31 ].…”
Section: Methodsmentioning
confidence: 99%